New predictive value of optical coherence tomography analysis in the diagnosis of idiopathic intracranial hypertension - Sajjadi, F; Khoshnevisan, MH; Doane, JF; Sajjadi, H (Journal of Contemporary Medical Sciences, 2017)
Objective Idiopathic Intracranial Hypertension (IIH) was first reported in 1897 as â€œPseudo tumor Cerebriâ€ when lumbar puncture was initiated in medicine. However, it is still a challenging diagnosis for many neurologists and ophthalmologists. Likewise, the sequela of IIH can be debilitating overall health and quality of life in most patients. This report presents the evolving diagnostic modalities that are different from mainstream IIH reports on gender, obesity and headaches ratios. We believe, using standard optical coherence tomography (OCT) can allow for a much earlier and more accurate diagnosis of IIH, with marked reduction in visual loss morbidity. Methods Retrospective, observational method was used to review 171 patientsâ€™ charts with suspected IIH over the past 12 years. The OCT of optic nerve and Macula was conducted by considering a list of signs and symptoms. Brain MRI, lumbar puncture, and our standard laboratory workups for optic neuropathies and visual fields were done. Visual Evoked Potentials were performed by neurologists. For purpose of this paper all IIH diagnosis fit Dandy diagnosis criteria of pseudo tumor cerebri as having a normal MRI. Results We evaluated 164 cases that had LPs done due to our proposed OCT Patterns to rule out IIH with no bio-microscopic evidence of overt papilledema. The majority of LP positive patients had some degree of visual field damage. Twenty out of 164 cases had false positive OCTs (with negative LPs) 88% accuracy in OCT diagnosis of IIH. No false positive OCT in Pattern-I. Conclusion Four different OCT diagnostic Patterns presented for IIH cases. The demographics of the patients considered having IIH by OCT Patterns I-IV and proven by positive LP; do not fit the classic demographic patterns. Classically, IIH has been reported to be observed in obese females with headaches and visible papilledema. Our findings put this classic set of presenting signs into question.